Ibn al-'Arabi on the One Who Is Transcendent (al-Ahad) and Immanent (al-Wahid) - Badron, Mohd Sani (Afkar: Jurnal Akidah dan Pemikiran Islam, 2011)
This article begins with Ibn al-‘Arabi’s discourse on “oneness” that belongs to every existent. Then, it presents Ibn al-‘Arabi’s interpretation of the oneness of God (Allah), viz. His Essential Oneness—whose dual aspects are ahadiyyah and wahidiyyah—and its relation to worship and submission to God, by mankind through Religion.